A situational analysis of child-headed households in South Africa - S. M. Mogotlane; M. E. Chauke; G. H. van Rensburg; S. P. Human; C. M. Kganakga (AOSIS, 2010)
The aftermath of the HIV and AIDS pandemic has resulted in great suffering in terms of loss of income, poor quality of life, morbidity and mortality, with children being destitute and orphaned at an alarming rapid rate. Families and communities are currently unable to cope with the effects of HIV and AIDS with special emphasis on the care and support of the affected orphans and vulnerable children, who as a result have been compelled to look after themselves giving rise to a new type of family, the child-headed household. The emergence of this type of family requires government's response in terms of care and support. The purpose of this study was to provide a broad picture of the location, prevalence, composition, functions, needs and challenges of child-headed households in South Africa, and explore available and required services, resources and safety nets for children in child-headed households. An exploratory and descriptive design was used for the purpose. The sample consisted of children heading households and those living in the households that are headed by children; government departments responsible for child welfare, such as, the Departments of Social Development, Health, Education and Agriculture; non-profit organisations and communities where these households are predominant. From the data collected, it was found that the rights of the affected children were compromised. Those heading the households were often not at school and were responsible for domestic chores. The households needed food, clothes, money, shelter, and education. Government in attempting to address these needs required clear policies which will provide a distinction between orphaned and vulnerable children and child-headed households.The study recommended a collaborative approach as it was shown that there was no single model of best practice to appropriately and effectively address the needs of child-headed households.